The prescription of penal actions and operations resulting from canon delicts violation - BOREK , DARIUSZ (Prawo Kanoniczne, 2019)
Violations constituting canon delicts incur certain legal effects, both penal and non penal. Among strictly penal effects one can find a possibility to call a perpetrator to account. In order to do this The Canon Law Code of 1983 classifies two types of actions connected with the committed delict: a criminal action (actio criminalis) and an action to execute a penalty (action ad poenam exsequendam), or a penal action. A violation which is a crime may result in other, non penal effects such as an action to repair the damage caused by the crime (actio ad damna reparanda), a declaration of an obstacle to ordination, or a dismissal from a religious institute. The prescription, which is the subject of this article, is thus connected with different possible effects incurred by a violation constituting a canon delict. Keeping all those possible consequences of violations constituting canon delicts, it seems legitimate to establish the matter of the prescription. Trying to find the answers to these questions, the author tries to focus on the followingissues:1.Prescription.1.1.Introductoryissues. 1.2.Principalterms and elements. 2. Prescription within penal responsibility 2.1. Imposing and executing a penalty. 2.2. Declaring a penalty. 2.3. Delicts reserved to the Congregation for the Doctrine of the Faith. 3. Prescription within civil and disciplinary responsibility 3.1. Action to repair damage. 3.2. Dismissal from a religious institute.